Amide-linked Ethanolamine Conjugate of Gemfibrozil as a Profound HDL Enhancer: Design, Synthesis, Pharmacological Screening and Docking Study - Rai, Himanshu; S. Dhaneshwar, Suneela (Current Drug Discovery Technologies, 2015)
Elevated concentration of any or all types of lipids in the plasma including hypertriglyceridemia and hypercholesterolemia leads to atherosclerotic cardiovascular disease. Effective medication needs multiple drug therapy as recommended cholesterol and triglyceride levels are difficult to achieve by monotherapy and frequently require the use of more than one lipid-lowering medication. Gemfibrozil lowers plasma triglyceride-rich lipoproteins mainly VLDL and increases HDL. It is associated with short plasma half-life (1.5h) and GIT distress on long term use. In a study it was found that ethanolamine decreases serum cholesterol, especially VLDL cholesterol and LDL cholesterol in rats fed an HF/HC diet. In the present work, we thought of exploring the effect of co-drug of gemfibrozil with ethanolamine (GE-I) as a potential combination therapy for the management of mixed hyperlipidemia. Synthesis of GE-I was effected by CDI coupling. Structure was confirmed spectrally. Interestingly kinetic studies revealed that GE-I resisted chemical and enzymatic hydrolysis. In tritoninduced hyperlipidemia, significant lowering of serum lipid levels was observed. The hallmark of GEI was its profound effect on HDL level which was raised above the normal level by 15%. Docking study also supported modulatory effect of GE-I (docking score -7.012) on PPAR-α which was comparable to docking score of gemfibrozil (-9.432). These preliminary observations prompt us to consider GE-I as a novel, serendipitous, hybrid anti-hyperlipidemic new chemical entity which needs be studied extensively to prove it as an HDL enhancing anti-hyperlipidemic agent.
Keywords: HDL enhancer